Influence of Gender on Interest and Academic Achievement of Students in Integrated Science in Obio Akpor Local Government Area of Rivers State - Godpower-Echie Glory; Ihenko, Sopuruchi (European Scientific Journal, ESJ, 2017)
The study looked at the influence of gender on interest and achievement of integrated Science students in Obio Akpor local government area of Rivers State. Two research questions and two hypotheses were raised, the population comprised of all secondary school students in the local government area and a total of 600 students took part in the study. Two instruments were used to collect data: the test scores and a likert scale like interest scale. Mean, standard deviation and t-test were used to analyse the data. The findings showed that gender has a significant influence on the interest but does not have a significant influence on achievement of Integrated Science students. It was recommended: that Integrated Science teachers should teach in such a way as to rouse the interest of the students, students should be self motivated, find joy in learning in order to excel.